Prognostic value of thyroid hormones in acute ischemic stroke – a meta analysis. Issue 1 (December 2017) - Jiang, Xingjun; Xing, Hongyi; Wu, Jing; Du, Ruofei; Liu, Houfu; Chen, Jixiang; Wang, Ji; Wang, Chen; Wu, Yan
Abstract Previous studies on the association between thyroid hormones and prognosis of acute ischemic stroke (AIS) reported conflicting results. We conducted a meta-analysis to assess the prognostic value of thyroid hormones in AIS. The PubMed, EMBASE, and Cochrane library databases were searched through May 12, 2017 to identify eligible studies on this subject. Out of 2, 181 studies retrieved, 11 studies were finally included with a total number of 3, 936 acute stroke patients for analysis. Odds ratio (OR) for predicting poor outcome or standardized mean difference (SMD) of thyroid hormone levels with 95% confidence intervals (95% CI) obtained from the studies were pooled using Review Manager 5.3. From the results, in AIS, patients with a poor outcome had lower levels of triiodothyronine (T3) and higher thyroxine (T4). Pooled OR confirmed the same association. Our study provides statistical evidence supporting the utility of thyroid hormone levels in prognosis of acute stroke.